Fiber-reinforced high-performance geopolymer concrete as well as preparation method and application thereof
Through the introduction of modified fiber in the ground concentration, the problem of poor toughness and cracking of the existing ground polymer concrete and prone to cracks are solved. Construction materials.
Patent Information
- Application Number
- CN202411486922.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-23
AI Technical Summary
The existing polyconcrete has poor toughness and is prone to cracks, making it difficult to meet the requirements of high performance and sustainability.
The method of enhancement of fiber is used to modify the modified fiber (made of polyethylene fiber and polyethylene glycol fiber mixing material, and the steps of the ultrasonic treatment, the coupling agent treatment, and the epoxy resin response) and the molor, coal ash, slag residue The combination of quartz powder and other raw materials to prepare high -performance vertical concrete.
It significantly improves the tensile strength and toughness of concrete, reduces the density and width of cracks, and obtains high -performance concrete materials with high strength and high toughness.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete materials, and in particular to a fiber-reinforced high-performance geopolymer concrete and a preparation method and application thereof. Background Art
[0002] Concrete is the largest building material today, and high-performance concrete represents the development direction of concrete technology. In recent years, with the vigorous development of the domestic construction industry, the requirements for the strength and crack resistance of concrete consumed in the construction process have been continuously improved. However, the inherent weakness of concrete is that as the strength continues to increase, its toughness deteriorates, and its brittleness increases, which makes it easy to crack. The appearance and expansion of cracks will cause the performance to decrease, thus shortening the lifespan.
[0003] The term geopolymer was first proposed by French materials scientist Davidovits in 1976 as a new type of alkali-activated inorganic gelling material. Geopolymer is an inorganic polymer with a three-dimensional network structure composed of silicon-oxygen tetrahedrons and aluminum-oxygen tetrahedrons formed by alkali-activated solid powders rich in silicon and aluminum. Studies have shown that compared with silicate cement, geopolymer has the advantages of high strength, acid resistance, high surface hardness, fire resistance, good thermal stability, and the ability to solidify heavy metals. Despite this, geopolymer concrete is a heavy and brittle material that is prone to a large number of cracks. It does not meet people's sustainable and high-performance requirements for the use of new materials, which limits its application in construction engineering materials. Therefore, the development of geopolymer high-performance concrete with both high strength and high ductility is of great significance to the future development direction of concrete technology. Summary of the invention
[0004] The main purpose of the present invention is to provide a fiber-reinforced high-performance geopolymer concrete and a preparation method and application thereof, so as to solve the problem that the geopolymer concrete in the prior art has poor toughness and is prone to cracks.
[0005] In order to achieve the above object, according to one aspect of the present invention, there is provided a fiber-reinforced high-performance geopolymer concrete, comprising the following raw materials: fly ash, slag, quartz powder, alkali activator, barium chloride, water and modified fiber;
[0006] The mass ratio of fly ash, slag, quartz powder, alkali activator, barium chloride and water is 620.3-849.7: 364.1-620.3: 242.8-248.1: 485.5-496.2: 72.8-74.3: 12.1-12.4;
[0007] The content of the modified fiber is 1% to 2% by volume of the fiber-reinforced high-performance geopolymer concrete;
[0008] The modified fiber is prepared by the following steps:
[0009] Step S01, placing the fiber material in an ethanol aqueous solution for ultrasonic treatment;
[0010] Step S02, adding a first silane coupling agent to the system after ultrasonic treatment and adjusting the pH of the system to 5.5-6.5;
[0011] Step S03, adding a second silane coupling agent to the system after adjusting the pH, stirring and reacting at 40-50° C. for 2-3 hours, then adding bisphenol A epoxy resin, and continuing to stir for 1-2 hours to obtain modified fiber;
[0012] The fiber material is a mixture of polyethylene fiber and polyvinyl alcohol fiber, and the volume ratio of the polyethylene fiber to the polyvinyl alcohol fiber is (1-3):1.
[0013] Furthermore, the diameter of the polyethylene fiber is 15 to 25 μm, the length of the polyethylene fiber is 10 to 14 mm, the tensile strength of the polyethylene fiber is 2400 to 2600 MPa, and the elastic modulus of the polyethylene fiber is 110 to 130 Gpa.
[0014] Furthermore, the diameter of the polyvinyl alcohol fiber is 10-20 μm, the length of the polyvinyl alcohol fiber is 10-14 mm, the tensile strength of the polyvinyl alcohol fiber is 1700-1900 MPa, and the elastic modulus of the polyvinyl alcohol fiber is 40 GPa.
[0015] Furthermore, the first silane coupling agent is selected from one or more of trimethoxysilane, 3-aminopropyltrimethoxysilane, and 3-methoxypropyltrimethoxysilane.
[0016] Furthermore, the second silane coupling agent is selected from one or more of trimethoxysilane, 3-aminopropyltrimethoxysilane, and 3-methoxypropyltrimethoxysilane.
[0017] Furthermore, the power of the ultrasonic treatment was 0.5 W / cm 2 ~1W / cm 2 , time is 5 to 10 minutes.
[0018] Furthermore, the mass fraction of ethanol in the ethanol aqueous solution is 70% to 80%.
[0019] Furthermore, in terms of weight percentage of the fly ash, the content of SiO2 in the fly ash is 50% to 55%, the content of Al2O3 is 30% to 32%, and the content of CaO is 3% to 5%.
[0020] Preferably, the fly ash has a specific gravity of 2 to 2.5 and a particle size of 40 to 60 μm.
[0021] Furthermore, in terms of weight percentage of the slag, the content of SiO2 in the slag is 32% to 36%, the content of Al2O3 is 16% to 20%, and the content of CaO is 33% to 35%.
[0022] Preferably, the specific gravity of the slag is 2.5 to 3, and the particle size is 10 to 20 μm.
[0023] Preferably, the mass ratio of fly ash to slag is (1-1.5):1.
[0024] Furthermore, the mass ratio of the fiber material, ethanol in the ethanol aqueous solution, the first silane coupling agent, the second silane coupling agent and the bisphenol A epoxy resin is 20-30:50:1-5:1-5:1-10.
[0025] Furthermore, the alkali activator is obtained by mixing a sodium silicate solution with a modulus of 2 to 2.5 and a 8 to 12 mol / L sodium hydroxide solution in a volume ratio of (1.5 to 2.5):1, and the content of SiO2 in the sodium silicate solution is 20% to 40% by weight percentage of the sodium silicate solution.
[0026] According to another aspect of the present invention, there is provided a method for preparing the above fiber-reinforced high-performance geopolymer concrete, comprising the following steps:
[0027] Step S1, mixing barium chloride, fly ash, slag and quartz powder to obtain a mixture;
[0028] Step S2, adding an alkaline activator and water to the mixture in sequence under stirring to obtain a mixture;
[0029] Step S3, adding modified fibers into the mixture, stirring and mixing to obtain fiber-reinforced high-performance geopolymer concrete.
[0030] Preferably, in step S1, the stirring speed is 76-80 r / min, and the stirring time is 2-5 min.
[0031] Preferably, in step S2, alkaline activator and water are added in sequence within 1 to 2 minutes at a rotation speed of 76 to 80 r / min. After the addition is completed, the rotation speed is adjusted to 135 to 140 r / min and stirred for 1 to 2 minutes to obtain a mixture.
[0032] Preferably, in step S3, the modified fiber is added to the mixture within 1 to 2 minutes at a rotation speed of 76 to 80 r / min, and then stirred for 1 to 2 minutes at 76 to 80 r / min to obtain fiber-reinforced high-performance geopolymer concrete.
[0033] According to another aspect of the present invention, there is provided the use of the fiber-reinforced high-performance geopolymer concrete as above or the fiber-reinforced high-performance geopolymer concrete prepared according to the above method in construction.
[0034] According to another aspect of the present invention, there is provided a building material, comprising the fiber-reinforced high-performance geopolymer concrete as described above or a hardened product of the fiber-reinforced high-performance geopolymer concrete prepared according to the method as described above.
[0035] Preferably, the fiber-reinforced high-performance geopolymer concrete is poured into a mold and moved to a vibration table for vibration molding. The molded concrete surface is smoothed and then covered with a film for curing for 24 to 28 hours. After demolding, it is cured for 24 to 32 days at a temperature of 18° C. to 22° C. and a relative humidity of 92% to 98% to obtain a hardened product.
[0036] By applying the technical solution of the present invention, waste materials such as slag and coal ash are used as the main raw materials, and by mixing the raw materials and modified polyethylene fibers and modified polyvinyl alcohol fibers, a high-performance geopolymer concrete with high tensile strength and good toughness is prepared; wherein, the introduction of modified polyethylene fibers can improve the tensile toughness of concrete materials, but the improvement of the initial crack stress is limited, and excessive addition of modified polyethylene fibers easily causes an increase in the density of cracks in the initial crack concrete products; and the addition of modified polyvinyl alcohol alone can improve the initial crack stress of concrete materials and reduce the density of cracks in the initial crack concrete products, but it will significantly reduce the tensile toughness of concrete and increase the width of cracks in the initial crack concrete products. The two are used in combination and by mixing the two, the synergistic effect of the two on strength and toughness in the crack-blocking process is brought into play, and a high-performance geopolymer concrete with high tensile strength and good toughness is prepared. In addition, the fiber-reinforced high-performance geopolymer concrete of the present invention is simple to prepare, has low requirements on equipment and production conditions, and has low difficulty in industrial production.
[0037] By adopting the fiber-reinforced high-performance geopolymer concrete of the present invention, a concrete material having both high toughness and high strength mechanical properties can be obtained, and the process is simple and has broad application prospects. DETAILED DESCRIPTION
[0038] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application may be combined with each other.
[0039] As described in the background technology, there are problems in the prior art that geopolymer concrete has poor toughness and is prone to cracks. In order to solve the above problems, according to one aspect of the present invention, a fiber-reinforced high-performance geopolymer concrete is provided, comprising the following raw materials: fly ash, slag, quartz powder, alkali activator, barium chloride, water and modified fiber; the mass ratio of fly ash, slag, quartz powder, alkali activator, barium chloride and water is 620.3-849.7: 364.1-620.3: 242.8-248.1: 485.5-496.2: 72.8-74.3: 12.1-12.4; the mass ratio of the fiber-reinforced high-performance geopolymer concrete is 1:1. In percentage, the content of the modified fiber is 1% to 2%; the modified fiber is prepared by the following steps: step S01, placing the fiber material in an ethanol aqueous solution for ultrasonic treatment; step S02, adding a first silane coupling agent to the system after ultrasonic treatment and adjusting the pH of the system to 5.5 to 6.5; step S03, adding a second silane coupling agent to the system after the pH adjustment, stirring and reacting at 40 to 50° C. for 2 to 3 hours, then adding bisphenol A type epoxy resin, and continuing to stir for 1 to 2 hours to obtain the modified fiber; the fiber material is a mixture of polyethylene fiber and polyvinyl alcohol fiber, and the volume ratio of polyethylene fiber to polyvinyl alcohol fiber is (1 to 3):1.
[0040] In order to obtain a tough and high-strength concrete material, the present invention provides a fiber-reinforced high-performance geopolymer concrete, which uses waste materials such as slag and fly ash as main raw materials and prepares high-performance geopolymer concrete with high tensile strength and good toughness through raw material ratio and the addition of modified polyethylene fiber and modified polyvinyl alcohol fiber; wherein, the introduction of modified polyethylene fiber can improve the tensile toughness of concrete materials, but the improvement of initial crack stress is limited, and excessive addition of modified polyethylene fiber is likely to increase the crack density in the initial crack concrete product; and the addition of modified polyvinyl alcohol alone can improve the initial crack stress of concrete materials and reduce the crack density in the initial crack concrete product, but it will significantly reduce the tensile toughness of concrete and increase the crack width in the initial crack concrete product. The two are used in combination and by ratioing the two, the synergistic effect of the two on strength and toughness in the crack resistance process is brought into play, so as to prepare high-performance geopolymer concrete with high tensile strength and good toughness; wherein, PVA fiber is placed in an ethanol aqueous solution and Ultrasonic treatment is performed. On the one hand, the microscopic roughness of the fiber surface is increased by the mechanical vibration of ultrasound, thereby improving the surface activity. A first silane coupling agent is added and the pH value is controlled. The first silane coupling agent forms a silanol group through a hydrolysis reaction in an aqueous environment. On the one hand, it reacts with the hydroxyl group on the fiber surface to condense to form a stable Si-OC bond structure, and on the other hand, it is used to participate in subsequent reactions; the added second silane coupling agent reacts with the generated silanol group to form a Si-O-Si bond, forming a two-dimensional cross-linked network on the fiber surface, and the bisphenol A epoxy resin reacts with the active groups on the polyvinyl alcohol fiber to form a three-dimensional cross-linked network to obtain modified PVA fiber. The modified PVA fiber can react with silicates in fly ash and the like to improve the bonding strength between the modified fiber and concrete in a chemical bonding manner; in the process of PVA fiber modification, polyethylene fiber is introduced and modified along with the PVA fiber, which is beneficial to improving the uniformity of dispersion of PVA fiber and PE fiber in the modified fiber and improving the mechanical properties of concrete materials.
[0041] In order to improve the load capacity of the concrete material and the uniformity of fiber dispersion, and improve the strength and toughness of the concrete material, in some embodiments, the diameter of the polyethylene fiber is 15-25 μm, the length of the polyethylene fiber is 10-14 mm, the tensile strength of the polyethylene fiber is 2400-2600 MPa, and the elastic modulus of the polyethylene fiber is 110-130 Gpa;
[0042] In order to further improve the strength and toughness of the concrete material, in some embodiments, the diameter of the polyvinyl alcohol fiber is 10-20 μm, the length of the polyvinyl alcohol fiber is 10-14 mm, the tensile strength of the polyvinyl alcohol fiber is 1700-1900 MPa, and the elastic modulus of the polyvinyl alcohol fiber is 40 GPa.
[0043] In some embodiments, the first silane coupling agent is selected from one or more of trimethoxysilane, 3-aminopropyltrimethoxysilane, and 3-methoxypropyltrimethoxysilane.
[0044] In some embodiments, the second silane coupling agent is selected from one or more of trimethoxysilane, 3-aminopropyltrimethoxysilane, and 3-methoxypropyltrimethoxysilane.
[0045] In some embodiments, the power of the ultrasonic treatment is 0.5 W / cm 2 ~1W / cm 2 , time is 5 to 10 minutes, in order to obtain higher surface activity of the fiber material.
[0046] In some embodiments, the mass fraction of ethanol in the ethanol aqueous solution is 70% to 80%.
[0047] In some embodiments, the components and proportions of fly ash and slag affect the fluidity, tensile toughness and compressive strength of the concrete mixture. In order to facilitate molding and obtain concrete materials with higher tensile toughness and compressive strength, the content of SiO2 in the fly ash is 50% to 55%, the content of Al2O3 is 30% to 32%, and the content of CaO is 3% to 5%, calculated as a percentage of the weight of the fly ash; preferably, the specific gravity of the fly ash is 2 to 2.5, and the particle size is 40 to 60 μm; preferably, the content of SiO2 in the slag is 32% to 36%, the content of Al2O3 is 16% to 20%, and the content of CaO is 33% to 35%, calculated as a percentage of the weight of the slag; preferably, the specific gravity of the slag is 2.5 to 3, and the particle size is 10 to 20 μm; preferably, the mass ratio of fly ash to slag is (1 to 1.5): 1, so as to obtain higher tensile toughness and compressive strength.
[0048] In some embodiments, the mass ratio of the fiber material, the ethanol in the ethanol aqueous solution, the first silane coupling agent, the second silane coupling agent, and the bisphenol A epoxy resin is 20-30:50:1-5:1-5:1-10.
[0049] In some embodiments, the alkaline activator is obtained by mixing a sodium silicate solution with a modulus of 2 to 2.5 and an 8 to 12 mol / L sodium hydroxide solution in a volume ratio of (1.5 to 2.5): 1, and the content of SiO2 in the sodium silicate solution is 20% to 40% as a percentage by weight of the sodium silicate solution; preferably, a sodium silicate solution with a modulus of 2 to 2.5 is mixed with a 10 mol / L sodium hydroxide solution in a volume ratio of 2: 1, sealed after sufficient stirring, and stored for cooling to obtain an alkaline activator.
[0050] According to another aspect of the present invention, a method for preparing the above fiber-reinforced high-performance geopolymer concrete is provided, comprising the following steps: step S1, mixing barium chloride, fly ash, slag, and quartz powder to obtain a mixture; step S2, adding an alkaline activator and water to the mixture in sequence under stirring conditions to obtain a mixture; step S3, adding modified fibers to the mixture, stirring and mixing to obtain fiber-reinforced high-performance geopolymer concrete. The preparation method of the present invention only requires mixing the components to obtain the fiber-reinforced high-performance geopolymer concrete, and the process is simple; preferably, in step S1, the stirring The rotation speed is 76-80 r / min, and the stirring time is 2-5 min. Preferably, in step S2, at a rotation speed of 76-80 r / min, alkaline activator and water are added in sequence within 1-2 min. After the addition is completed, the rotation speed is adjusted to 135-140 r / min and stirred for 1-2 min to obtain a mixture. Preferably, in step S3, at a rotation speed of 76-80 r / min, modified fibers are added to the mixture within 1-2 min, and then stirred at 76-80 r / min for 1-2 min to obtain fiber-reinforced high-performance geopolymer concrete.
[0051] According to another aspect of the present invention, there is provided a building material, comprising the above concrete or a hardened product of the fiber-reinforced high-performance geopolymer concrete prepared according to the above method.
[0052] Preferably, the fiber-reinforced high-performance geopolymer concrete is poured into a mold and moved to a vibration table for vibration molding. The molded concrete surface is smoothed and then covered with a film for curing for 24 to 28 hours. After demolding, it is cured for 24 to 32 days at a temperature of 18° C. to 22° C. and a relative humidity of 92% to 98% to obtain a hardened product.
[0053] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0054] Unless otherwise specified, the raw materials or reagents used in the examples and comparative examples are all commercially available. Among them, the components and parameters of some raw materials in the examples and comparative examples of the present invention are as follows: fly ash is Class F fly ash produced by Gongyi Longze Water Purification Material Co., Ltd., with a specific gravity of 2.3 and an average particle size of 53.80 μm. The specific chemical composition and content (the weight percentage of each component in the fly ash) are shown in Table 1; slag is blast furnace S105 slag produced by Gongyi Longze Water Purification Material Co., Ltd., with a specific gravity of 2.9 and an average particle size of 15.44 μm. The specific chemical composition and content (the weight percentage of each component in the slag) are shown in Table 2; polyethylene fiber is commercially available from DSM. The physical properties of the polyethylene fiber are shown in Table 3; the polyvinyl alcohol fiber is a commercial product of Changzhou Tianyi Engineering Fiber Co., Ltd., and the physical properties of the polyvinyl alcohol fiber are shown in Table 4; the water glass (sodium silicate solution) is a commercial product of Jiashan Yourui Refractory Material Co., Ltd., and its main parameters are shown in Table 5; the sodium hydroxide is a flaky sodium hydroxide with a purity of 96% produced by Xilong Science Co., Ltd.; the quartz sand is ordinary river sand, No. 9 sand, with a specific gravity of 2.65 and an average diameter of 110 μm; the bisphenol A epoxy resin is a commercial product of Dongduoju Chemical Co., Ltd., with a brand name of DER-332.
[0055] Table 1. Chemical composition of fly ash
[0056]
[0057] Table 2. Chemical composition of slag
[0058] chemical composition CaO <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[SO3]]> <![CDATA[Fe2O3]]> MgO other content(%) 34.00 34.50 17.70 1.64 1.03 6.01 5.12
[0059] Table 3. Physical properties of polyethylene fibers
[0060]
[0061] Table 4. Physical properties of polyvinyl alcohol fibers
[0062]
[0063] Table 5. Main parameters of water glass
[0064] Modulus <![CDATA[Density (g / cm 3 )]]> <![CDATA[SiO2(%)]]> <![CDATA[Na2O(%)]]> 2.25 1.5 29.99 13.75
[0065] Example 1
[0066] A method for preparing a hybrid PE-PVA fiber reinforced high-performance geopolymer concrete:
[0067] Step 1, preparation of modified fiber, the specific steps are as follows:
[0068] Step 1.1: Place the fiber material in an ethanol-water solution at 0.5 W / cm2 Ultrasonic treatment for 5 minutes; wherein the mass fraction of ethanol in the ethanol aqueous solution is 75%;
[0069] Step 1.2, adding trimethoxysilane to the system after ultrasonic treatment and adjusting the pH of the system to 6;
[0070] Step 1.3, adding 3-methoxypropyltrimethoxysilane to the system after adjusting the pH, stirring and reacting at 40° C. for 2 h, adding bisphenol A epoxy resin, and continuing to stir for 1 h to obtain modified fiber;
[0071] The mass ratio of the fiber material, ethanol in the ethanol aqueous solution, trimethoxysilane, 3-methoxypropyltrimethoxysilane and bisphenol A epoxy resin is 20:50:2:2:5;
[0072] Step 2: concrete preparation. The specific steps are as follows:
[0073] Step 2.1, mix barium chloride, fly ash, slag and quartz powder, and stir at a speed of 76 r / min for 2 min;
[0074] Step 2.2, continue stirring at a speed of 76 r / min for 1 min and add alkaline activator and water in sequence during the stirring process. After the stirring process is completed, adjust the speed to 135 r / min and stir quickly for 1 min to obtain a mixture;
[0075] Step 2.3, adjusting the rotation speed to 76 r / min for stirring, adding the modified fiber to the mixture within 1 minute, and then stirring for 1 minute at 76 r / min to obtain fiber-reinforced high-performance geopolymer concrete; wherein the modified fiber is added in an amount of 2% by volume of the fiber-reinforced high-performance geopolymer concrete;
[0076] The alkaline activator is prepared by the following method: a sodium silicate solution with a modulus of 2.25 is mixed with a 10 mol / L sodium hydroxide solution in a volume ratio of 2:1, the mixture is sealed after being fully stirred, and stored for cooling before being used for pouring;
[0077] The mass ratio of fly ash, slag, quartz powder, alkali activator, barium chloride and water is 849.7:364.1:242.8:485.5:72.8:12.1;
[0078] The fiber material is a mixture of polyethylene fiber and polyvinyl alcohol fiber in a volume ratio of 3:1.
[0079] Example 2
[0080] The difference between it and Example 1 is that in step 1, the fiber material is a mixture of polyethylene fiber and polyvinyl alcohol fiber in a volume ratio of 2:1.
[0081] Example 3
[0082] The difference between it and Example 1 is that in step 1, the fiber material is a mixture of polyethylene fiber and polyvinyl alcohol fiber in a volume ratio of 1:1.
[0083] Example 4
[0084] The difference between it and Example 1 is that in step 2, the mass ratio of fly ash, slag, quartz powder, alkali activator, barium chloride and water is 736.3:490.9:245.4:490.9:73.6:12.3.
[0085] Example 5
[0086] The difference between it and Example 1 is that in step 2, the mass ratio of fly ash, slag, quartz powder, alkali activator, barium chloride and water is 620.3:620.3:248.1:496.2:74.3:12.4.
[0087] Comparative Example 1
[0088] The difference between this embodiment and Example 1 is that in step 1, the fiber materials are all polyethylene fibers, and the content of the modified fibers is 1%.
[0089] Comparative Example 2
[0090] The difference between this embodiment and Example 1 is that in step 1, all fiber materials are polyethylene fibers, and the content of modified fibers is 1.5%.
[0091] Comparative Example 3
[0092] The difference between this embodiment and Example 1 is that in step 1, the fiber materials are all polyethylene fibers, and the content of the modified fibers is 2.0%.
[0093] Comparative Example 4
[0094] The difference between it and Example 1 is that in step 1, the fiber material is a mixture of polyethylene fiber and polyvinyl alcohol fiber in a volume ratio of 1:3.
[0095] Comparative Example 5
[0096] The difference between it and Example 1 is that in step 1, the fiber materials are all polyvinyl alcohol fibers.
[0097] Comparative Example 6
[0098] The difference between this embodiment and Example 1 is that in step 2, no fiber material is added during the concrete preparation process. The specific steps are as follows:
[0099] Step 1.1, mix barium chloride, fly ash, slag and quartz powder, and stir at a speed of 76 r / min for 2 min;
[0100] Step 1.2, continue stirring at a speed of 76 r / min for 1 min and add alkaline activator and water in sequence during the stirring process. After the stirring process is completed, adjust the speed to 135 r / min and stir quickly for 1 min to obtain a mixture;
[0101] Step 1.3, adjusting the rotation speed to 76 r / min for stirring, and then stirring at 76 r / min for 1 min to obtain geopolymer concrete;
[0102] Wherein, the base activator is prepared by the following method:
[0103] Mix the sodium silicate solution with a modulus of 2.25 and the 10 mol / L sodium hydroxide solution in a volume ratio of 2:1, stir thoroughly, seal, store until cooled, and use for pouring;
[0104] Among them, the mass ratio of fly ash, slag, quartz powder, alkali activator, barium chloride and water is 849.7:364.1:242.8:485.5:72.8:12.1.
[0105] Comparative Example 7
[0106] The difference between the embodiment 1 and the embodiment 1 is that in step 1, the fiber modification is not performed, and the concrete is directly prepared with polyethylene fiber and polyvinyl alcohol fiber. The specific steps are as follows:
[0107] Step 1.1, barium chloride, fly ash, slag and quartz powder were mixed, and stirred at a speed of 76 r / min for 2 min;
[0108] Step 1.2, continue stirring at a speed of 76 r / min for 1 min and add alkaline activator and water in sequence during the stirring process. After the stirring process is completed, adjust the speed to 135 r / min and stir quickly for 1 min to obtain a mixture;
[0109] Step 1.3, adjusting the rotation speed to 76 r / min for stirring, adding the fiber material to the mixture within 1 minute, and then stirring at 76 r / min for 1 minute to obtain fiber-reinforced high-performance geopolymer concrete;
[0110] Wherein, the base activator is prepared by the following method:
[0111] Mix a sodium silicate solution with a modulus of 2.25 with a 10 mol / L sodium hydroxide solution in a ratio of 2:1. Mix the prepared sodium hydroxide solution with the sodium silicate solution, stir thoroughly, reseal, store until cooled, and use for pouring;
[0112] The mass ratio of fly ash, slag, quartz powder, alkali activator, barium chloride and water is 849.7:364.1:242.8:485.5:72.8:12.1;
[0113] The fiber material is a mixture of polyethylene fiber and polyvinyl alcohol fiber in a volume ratio of 3:1.
[0114] The performance tests were performed on the concrete prepared in Examples 1-5 and Comparative Examples 1-7:
[0115] 1. Static tensile test
[0116] The static axial tension specimen was designed according to JCT2461-2018. The static tensile test was carried out according to the Test Method for Mechanical Properties of High Ductility Fiber Reinforced Cement-Based Composite Materials (Specification). A microcomputer-controlled electronic universal testing machine was used for the test. The initial crack stress and tensile toughness are shown in Table 6.
[0117] Crack width and density measurement: A relatively uniform crack distribution segment was taken from the initial crack specimen in the static tensile test and a marking operation was performed with a marking length of 30 mm. Within this interval, a microscope was used to measure the crack width and number. The test results of the average crack width and average crack density (i.e., the number of cracks per unit length) are shown in Table 7.
[0118] 2. Axial static compression test
[0119] The static axial compression specimens were designed according to the standard “Standard Test Methods for Mechanical Properties of Ordinary Concrete” ASTM-C39. The axial static compression test was carried out according to the ASTM-C39 standard using a voltage servo force testing machine (model MATEST C088-01). The compressive strength and elastic modulus of the specimens are shown in Table 8.
[0120] Table 6. Test results of initial crack stress and tensile toughness of concrete materials
[0121]
[0122]
[0123] It can be seen from Table 6 that the concrete prepared in Examples 1-5 has both high initial crack stress and tensile toughness. In the concrete material, the increase in the amount of modified polyethylene fiber can effectively improve the tensile toughness of the concrete, and the addition of an appropriate amount of modified polyvinyl alcohol fiber can significantly increase the initial crack stress of the concrete while ensuring a high tensile toughness of the material, thereby obtaining a concrete material with both tensile toughness and tensile strength; in the concrete material, the addition of slag can increase the initial crack stress of the concrete material and significantly improve its tensile toughness.
[0124] It can be seen from Comparative Example 6 and Comparative Examples 1-3 that the addition of modified polyethylene fibers and the increase in the amount of added fibers can effectively improve the tensile toughness of concrete and, to a certain extent, improve the initial crack stress of concrete.
[0125] From Comparative Examples 6 and 5, it can be seen that the addition of modified polyvinyl alcohol alone increases the initial crack stress of the concrete material from 2.31 MPa to 3.10 MPa, but significantly reduces the tensile toughness of the concrete, which increases the tensile toughness of the concrete material from 14.20 kJ / m 3 Reduced to 0.43 kJ / m 3 .
[0126] It can be seen from Comparative Example 3 and Examples 1-3 that replacing a certain amount of modified polyethylene fibers with polyvinyl alcohol fibers can significantly increase the initial crack stress of concrete, and the resulting concrete has higher tensile toughness.
[0127] It can be seen from Comparative Example 4 and Examples 1-3 that excessive addition of polyvinyl alcohol fibers can lead to a significant decrease in the tensile toughness of concrete. For example, when the volume ratio of modified polyethylene fibers to polyvinyl alcohol fibers is 1:3 (see Comparative Example 4), the tensile toughness of concrete is only 1.71 kJ / m3.
[0128] It can be seen from Examples 3, 4 and 5 that the increase in slag content significantly improves the tensile toughness of concrete. Compared with Example 3, the tensile toughness of concrete in Examples 4 and 5 is increased by 16.6% and 11.9% respectively, and the tensile toughness of the concrete material is significantly improved.
[0129]
[0130]
[0131] It can be seen from Table 7 that the initial crack products of the concrete prepared in Examples 1-5 have smaller crack width and crack density. In the preparation of concrete materials, the addition of modified polyethylene fibers can reduce the width of the cracks, but as the amount of modified polyethylene fibers increases, the crack density will increase. The addition of modified polyvinyl alcohol fibers alone can reduce the crack density, but will cause a significant increase in the crack width. In the concrete prepared in Examples 1-5, by adding modified polyethylene fibers and polyvinyl alcohol fibers and adjusting the ratio of the two fibers, a better complementary effect can be achieved, thereby reducing the crack width and crack density of the concrete cracks.
[0132] It can be seen from Comparative Example 6 and Comparative Examples 1-3 that the addition of modified polyethylene fiber alone can reduce the width of the cracks, but as the amount of modified polyethylene fiber increases, the density of the cracks increases.
[0133] It can be seen from Comparative Examples 6 and 5 that the addition of modified polyvinyl alcohol alone can reduce the crack density of concrete materials, but will significantly increase the crack width.
[0134] It can be seen from Comparative Example 3 and Examples 1-3 that a concrete material having both low crack width and crack density can be obtained by replacing a certain amount of modified polyethylene fibers with polyvinyl alcohol fibers.
[0135] It can be seen from Comparative Example 4 and Examples 1-3 that adding too much polyvinyl alcohol fiber will increase the crack density.
[0136] Table 8. Compressive strength and elastic modulus test results of concrete materials
[0137]
[0138]
[0139] It can be seen from Table 6 that the concrete prepared in Examples 1-5 has high compressive strength and high elastic modulus; and it can be seen from Examples 3-5 that the compressive strength and elastic modulus of the concrete material increase with the increase of slag content, and the elastic modulus of the concrete in Example 5 is 23% higher than that in Example 3.
[0140] From the above description, it can be seen that the concrete prepared by the above-mentioned embodiments of the present invention has high initial crack stress, tensile toughness and high compressive strength, and the crack width and crack density of tensile cracking are low, and has good application prospects.
[0141] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A fiber-reinforced high-performance geopolymer concrete, characterized in that: The raw materials include fly ash, slag, quartz powder, alkali activator, barium chloride, water and modified fiber; The mass ratio of the fly ash, the slag, the quartz powder, the alkali activator, the barium chloride and the water is 620.3-849.7: 364.1-620.3: 242.8-248.1: 485.5-496.2: 72.8-74.3: 12.1-12.4; The content of the modified fiber is 1% to 2% by volume of the fiber-reinforced high-performance geopolymer concrete; The modified fiber is prepared by the following steps: Step S01, placing the fiber material in an ethanol aqueous solution for ultrasonic treatment; Step S02, adding a first silane coupling agent to the system after the ultrasonic treatment and adjusting the pH of the system to 5.5-6.5; Step S03, adding a second silane coupling agent to the system after adjusting the pH, stirring and reacting at 40-50° C. for 2-3 hours, then adding bisphenol A epoxy resin, and continuing to stir for 1-2 hours to obtain the modified fiber; The fiber material is a mixture of polyethylene fiber and polyvinyl alcohol fiber, and the volume ratio of the polyethylene fiber to the polyvinyl alcohol fiber is (1-3):
1.
2. The fiber-reinforced high-performance geopolymer concrete according to claim 1, characterized in that: The diameter of the polyethylene fiber is 15 to 25 μm, the length of the polyethylene fiber is 10 to 14 mm, the tensile strength of the polyethylene fiber is 2400 to 2600 MPa, and the elastic modulus of the polyethylene fiber is 110 to 130 Gpa; and / or, The diameter of the polyvinyl alcohol fiber is 10-20 μm, the length of the polyvinyl alcohol fiber is 10-14 mm, the tensile strength of the polyvinyl alcohol fiber is 1700-1900 MPa, and the elastic modulus of the polyvinyl alcohol fiber is 40 GPa; and / or, The power of the ultrasonic treatment was 0.5 W / cm 2 ~1W / cm 2 , time is 5 to 10 minutes; and / or, The mass fraction of ethanol in the ethanol aqueous solution is 70% to 80%.
3. The fiber-reinforced high-performance geopolymer concrete according to claim 1, characterized in that: The first silane coupling agent is selected from one or more of trimethoxysilane, 3-aminopropyltrimethoxysilane, and 3-methoxypropyltrimethoxysilane; and / or, The second silane coupling agent is selected from one or more of trimethoxysilane, 3-aminopropyltrimethoxysilane, and 3-methoxypropyltrimethoxysilane.
4. The fiber-reinforced high-performance geopolymer concrete according to claim 1, characterized in that: Calculated by weight percentage of the fly ash, the content of SiO2 in the fly ash is 50% to 55%, the content of Al2O3 is 30% to 32%, and the content of CaO is 3% to 5%; Preferably, the fly ash has a specific gravity of 2 to 2.5 and a particle size of 40 to 60 μm.
5. The fiber-reinforced high-performance geopolymer concrete according to claim 1, characterized in that: Calculated by weight percentage of the slag, the content of SiO2 in the slag is 32% to 36%, the content of Al2O3 is 16% to 20%, and the content of CaO is 33% to 35%; Preferably, the slag has a specific gravity of 2.5 to 3 and a particle size of 10 to 20 μm; Preferably, the mass ratio of the fly ash to the slag is (1-1.5):
1.
6. The fiber-reinforced high-performance geopolymer concrete according to claim 1, characterized in that: The mass ratio of the fiber material, the ethanol in the ethanol aqueous solution, the first silane coupling agent, the second silane coupling agent and the bisphenol A epoxy resin is 20-30:50:1-5:1-5:1-10.
7. The fiber-reinforced high-performance geopolymer concrete according to any one of claims 1 to 6, characterized in that: The alkaline activator is obtained by mixing a sodium silicate solution with a modulus of 2 to 2.5 and an 8 to 12 mol / L sodium hydroxide solution in a volume ratio of (1.5 to 2.5):1; the content of SiO2 in the sodium silicate solution is 20% to 40% in terms of weight percentage of the sodium silicate solution.
8. The method for preparing fiber-reinforced high-performance geopolymer concrete according to any one of claims 1 to 7, characterized in that: The steps include: Step S1, mixing barium chloride, fly ash, slag and quartz powder to obtain a mixture; Step S2, adding an alkaline activator and water to the mixture in sequence under stirring to obtain a mixture; Step S3, adding modified fibers to the mixture, stirring and mixing to obtain fiber-reinforced high-performance geopolymer concrete; Preferably, in step S1, the stirring speed is 76-80 r / min, and the stirring time is 2-5 min; Preferably, in the step S2, the alkaline activator and water are added in sequence within 1 to 2 minutes at a rotation speed of 76 to 80 r / min. After the addition is completed, the rotation speed is adjusted to 135 to 140 r / min and stirred for 1 to 2 minutes to obtain the mixture; Preferably, in the step S3, the modified fiber is added to the mixture within 1 to 2 minutes at a rotation speed of 76 to 80 r / min, and then stirred for 1 to 2 minutes at 76 to 80 r / min to obtain the fiber-reinforced high-performance geopolymer concrete.
9. Use of the fiber-reinforced high-performance geopolymer concrete according to any one of claims 1 to 7 or the fiber-reinforced high-performance geopolymer concrete prepared according to the method of claim 8 in construction.
10. A building material, characterized in that: A hardened product comprising the fiber-reinforced high-performance geopolymer concrete according to any one of claims 1 to 7 or the fiber-reinforced high-performance geopolymer concrete prepared according to the method of claim 8; Preferably, the fiber-reinforced high-performance geopolymer concrete is poured into a mold and moved to a vibration table for vibration molding. After the molded concrete surface is smoothed, the surface is covered with a film and cured for 24 to 28 hours. After demolding, it is cured for 24 to 32 days at a temperature of 18° C. to 22° C. and a relative humidity of 92% to 98% to obtain the hardened product.
Citation Information
Patent Citations
Ultrahigh-molecular-weight polyethylene fiber reinforced geopolymer-based composite and preparation method thereof
CN108529936A
Buoyancy ultrahigh molecular weight polyethylene fibers and preparation method thereof
CN110965145A
High-performance sound insulation coating and preparation method thereof
CN116102925A
Nano silicon dioxide and hybrid fiber reinforced geopolymer concrete capable of improving compressive strength and preparation method of nano silicon dioxide and hybrid fiber reinforced geopolymer concrete
CN116675478A
Super high-molecular weight polyethylene fiber excellent in adhesivity and method for manufacturing the same
JP2001262469A